Primary Squamous Cell Carcinoma of the Kidney: A Case Series - Noor Nabi Junejo; Muhammad Humza Kamal; Shahid Aquil; Fathiya Al Rahbi; Ghalib Amur Rashid Al Badaai; Khurram Mutahir Siddiqui (Oman Medical Journal)
Primary squamous cell carcinoma (SCC) of the renal parenchyma without a history of urolithiasis is a rare entity. Renal SCC is usually associated with other conditions like renal stone disease, chronic inflammation, and infection. We report three cases of primary SCC with no history of renal stone disease or identifiable risk factors. We also present a current review of the literature and a detailed description of the morphological features.